Influence Attitude and Behavioral Intention of the Millenial Generation to Adoption of Telemedicine Platforms in Bali in the New Normal Era - I Putu Kresna Saniscara Dewanta; A. A. N Eddy Supriyadinata Gorda; Gede Sri Darma; Luh Putu Mahyuni (International Journal of Social Science and Business, 2023)
The pandemic has brought various impacts and changes in people's lives, one of which is the use of digital telemedicine applications. Health is a vital aspect of human life; therefore, telemedicine applications have an important role in facing the changing era. This study attempts to describe the attitudes and behavioral intentions of the millennial generation in adopting telemedicine platforms in the new normal era. The data in this study were collected by distributing questionnaires to 120 respondents, namely the millennial generation in Bali. Data were analyzed using the SEM-PLS analysis technique. The results of this study found that perceived ease of use, social influence, perceived usefulness had a positive and significant effect on behavioral intention, while e-trust had no effect. Perceived ease of use has a positive and significant effect on perceived usefulness. Social influence has a positive and significant effect on E-trust. E-trust is not able to mediate the influence of social influence on behavioral intention. Perceived usefulness is able to positively mediate the effect of perceived ease of use on behavioral intention. This research is expected to provide an overview of consumer behavior towards digital services, as well as an evaluation for digital service providers themselves.